A new species of Simulium (Nevermannia) (Diptera, Simuliidae) from Thailand, with keys to members of the Simulium feuerborni species-group in Thailand - Hiroyuki, Takaoka (Pensoft Publishers, 2011)
Abstract. Simulium (Nevermannia) maeaiense sp. n. is described on the basis of female, male, pupal and larval specimens collected from Chiang Mai Province, Thailand. This species is assigned to the feuerborni species-group of the subgenus Simulium (Nevermannia), and is distinctive among this species-group in having the female cibarium furnished with numerous dark minute conical processes on the lower part, the female genital fork with a strongly sclerotized horizontal bar on each arm, and six long pupal gill filaments arising nearly at the same level from the common basal stalk and lying in a horizontal plane. Identification keys to seven species of the feuerborni species-group reported from Thailand are provided for females, males, pupae and mature larvae.